Bhutan Policy Notes : Doing Business Reform - World Bank (World Bank, Washington, DC, 2019)
Bhutan has been reforming its doing business environment in recent years as part of a policy shift to improving its investment climate and economic performance.Overall, it is ranked 75 out of 190 countries and is the highest ranked country in the South Asia region, significantly outperforming Bangladesh and Pakistan. In the last decade, as part of a Government policy agenda to improve competitiveness, Bhutan has launched across the board reforms in many areas.During the DB 2018 period, there was not a reform momentum in Bhutan. The very slight downgrading of the ranking can be attributed to reform inertia after a decade of success. Another factor for the lack of improvements in DC in 2018 has been Government focus on other reforms, especially involving hydropower, cottage and small industries and SOE’s.Reforms clearly need acceleration after a decade of strong reform momentum, spurred by desire to see improvements in Bhutan’s overall ranking has not moved significantly in either direction. There has been significant improvement in dealing with construction permits and in enforcing contracts but deterioration in protecting minority investors and registering property. The lack of forward momentum reflects slippages in reform momentum due to policy environment and shifting government priorities.First, access to credit in Bhutan is improving due to the expansion of the scope of collateralizable assets and the deepening of the credit bureaus. Second, the National Land Commission, a competent and responsible public agency managing land administration, has made progress in terms of land registration and online portals. According to the National Land Commission (NLC), the average days to register property declined from 54 days in 2016 to 42 days in 2018. Finally, recent Government attempts to streamline regulations and dismantle administrative complexities should help reduce transactions costs for private operators.top of these areas, Bhutan’s business climate remains constrained by imperfections in factor markets, limited access to product markets, and state dominance.The focus has been on ways to set up businesses, improve construction permits, improve credit bureaus, ensure better land registration, and protect minority investors. The Bank/IFC team is working in close collaboration with this new team and providing relevant international experience and support.